1999
DOI: 10.1289/ehp.99107521
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation of particulate air pollution and poor cardiac autonomic control in the elderly.

Abstract: examined the cardiac autonomic response to daily variations in PM in 26 elderly (mean age 81) individuals for 3 consecutive weeks. Several standardized methods were used to measure 24-hr average PM concentrations prior to the clinical test inside (indoor PM2.5) and immediately outside (outdoor PM2.5 and PM2.5-10) of participants' residences. Resting, supine, 6-min R wave to R wave (R-R) interval data were collected to estimate high frequency (0.15-0.40 Hz) and low frequency (0.04-0.15 Hz) powers and standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
219
8
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(248 citation statements)
references
References 31 publications
20
219
8
1
Order By: Relevance
“…These studies have found that the elderly with or without cardiovascular conditions, hypertension or diabetes may be more responsive to airborne particle exposure and have a larger reduction of the HRV in relation to an increase in PM 2.5 ambient concentrations (Liao et al, 1999;Pope et al, 1999Pope et al, , 2004bGold et al, 2000;Holguı´n et al, 2003). Our findings are consistent with those even though we studied young healthy adults; as expected, the magnitude of association was larger in those studies where susceptible individuals were included than in ours.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These studies have found that the elderly with or without cardiovascular conditions, hypertension or diabetes may be more responsive to airborne particle exposure and have a larger reduction of the HRV in relation to an increase in PM 2.5 ambient concentrations (Liao et al, 1999;Pope et al, 1999Pope et al, , 2004bGold et al, 2000;Holguı´n et al, 2003). Our findings are consistent with those even though we studied young healthy adults; as expected, the magnitude of association was larger in those studies where susceptible individuals were included than in ours.…”
Section: Discussionsupporting
confidence: 92%
“…All of them found that an increase in PM 2.5 or in PM 10 , alone or combined with other pollutants like ozone, were associated with a reduction of the SDNN and of the rMSSD, only one study informed an increase of this last index (Gold et al, 2000). Studies in which frequency domain indexes were used also found this association, particularly of the HF of a parasympathetic-related index (Liao et al, 1999;Holguı´n et al, 2003;Park et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The National Research Council ( NRC ) has suggested that understanding PM mass concentration measurement errors should be ranked as one of the 10 highest PM research priorities for the U.S. EPA ( NRC, 1998 ). Evaluating the magnitude of this error is important in determining the certainty of epidemiological findings related to matched PM exposure± health effect studies such as those currently being conducted by the U.S. EPA (Liao et al, 1999 ). Quantifying the uncertainties in PM mass measurements made by various monitors would also be useful in comparing exposure data among reported studies.…”
Section: Introductionmentioning
confidence: 99%